The The Colon Interposition as Esophageal Replacement in Long-Gap Esophageal Atresia - Ariyanta, Kadek Deddy; Darmajaya, I Made; Alexandra, Alexandra; Setiawan, Kelvin (JBN (Jurnal Bedah Nasional), 2022)
Background: Long-gap Esophageal Atresia (LGEA) remains one of the most challenging congenital conditions. When primary anastomoses attempts had failed, esophageal replacement (ER) is indicated in these patients. Some infants with LGEA are born with other congenital anomalies, such as rectourethral fistula. In this study, we reported our experience in managing newborn with LGEA and rectourethral fistula. Case : A 1-day-old male neonate complained of unable to swallow any breast milk and presence of feces-like discharge from external urethral orifice within 24 hours after birth. Oral gastric tube was unable to pass into the stomach and x-ray examination revealed curled gastric tube in esophagus, and there wasn’t any bubble seen from patient’s stomach. Patient then was diagnosed with long gap esophageal atresia without fistula. Esophageal replacements using left colon interposition technique was performed as closing and final procedure.  Gastrostomy tube insertion, sigmoid colostomy, and cervical esophagostomy were immediately performed. Posterior sagittal anorectoplasty (PSARP) for patient’s recto-urethral fistula were performed six months after sigmoid colostomy. Patient was hospitalized with total of 32 days and gastric feeding tube can be removed three months after surgery. Conclusion: colon interposition can be safely used in long gap esophageal atreasia although patient had undergone previous colostomy repair. Long-term follow up will be needed. Further large-scale studies regarding this matter are necessary and hopefully comprehensive treatment can be established in the future.